2019
DOI: 10.1177/0733464818821055
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consolidating AAA on the Delivery of HCBS: Evidence From Iowa

Abstract: In this study, the authors evaluate the 2013 consolidation of Iowa’s Area Agencies on Aging (AAA) on the delivery of home and community-based services (HCBS) to older adults in the state. A mixed-methods approach combined a quasi-experimental design using longitudinal service delivery data with qualitative analyses of surveys and interviews with AAA staff and clients. Overall, consolidation had no detectable effect on the proportion of older adults served by the AAAs. Subgroup analysis showed that consolidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Moreover, BIP provided no ongoing resources to support the sustainment of HIT tools. Consolidation of local or regional HCBS agencies as seen in some states (Arora et al, 2020) may facilitate economics of scale in terms of information technology and support ongoing investments to sustain the use of HIT. It will be informative to examine the extent to which BIP-related HIT interventions are sustained into the future and what resources states need to sustain HIT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BIP provided no ongoing resources to support the sustainment of HIT tools. Consolidation of local or regional HCBS agencies as seen in some states (Arora et al, 2020) may facilitate economics of scale in terms of information technology and support ongoing investments to sustain the use of HIT. It will be informative to examine the extent to which BIP-related HIT interventions are sustained into the future and what resources states need to sustain HIT.…”
Section: Discussionmentioning
confidence: 99%
“…One that has is a study in Iowa that assessed the impact of consolidating service agencies and found that, while there was no statistically significant impact on the proportion of the population served, the consolidation did lead to an increase in quality of services (Arora et al, 2020). While the object of the study differs from the Children's Design in that it was consolidating agencies and not waivers, the study does demonstrate the potential benefit of simplified access and streamlined services.…”
Section: Streamlined Accessmentioning
confidence: 99%
“…A national survey of OAA program recipients found that more than 85% of individuals receiving HCBS were able to remain at home, and without the relatively basic and inexpensive assistance from the HCBS to meet their needs, many would have been institutionalized (Arora et al, 2019). Remaining at home and aging-in-place significantly reduce nursing home, hospital admissions, and health care expenditures (Ferris et al, 2016).…”
Section: Introductionmentioning
confidence: 99%